Student perspectives on project-based learning using local wisdom orientation on botanical learning - Anggarani, Dinar Arsy; Sari, Murni Sapta; Sulisetijono, Sulisetijono (Biology Education Department, Universitas Insan Budi Utomo, Malang, Indonesia, 2025)
Botanical education in higher education often faces challenges in contextualizing abstract plant concepts and fostering student engagement. Integrating local wisdom into botanical education through Project-Based Learning (PjBL) enhances students’ learning experiences by connecting traditional ecological knowledge with scientific concepts. Brakseng, Batu Malang, provides an ideal setting for this approach, yet research on students' perceptions remains limited. This study aims to examine students’ perceptions of local wisdom-integrated PjBL in botanical education by analyzing its influence on conceptual understanding, learning motivation, and perceived implementation challenges. A cross-sectional survey was conducted from August to November 2024 with 63 undergraduate biology students at Universitas Negeri Malang. Data were collected through a Likert-scale questionnaire assessing learning experience, motivation, and performance, supplemented by qualitative responses. Quantitative data were analyzed using statistical software SPSS, while qualitative data were examined through thematic analysis. Results indicate that PjBL integrated with local wisdom received a positive responses regarding student learning, motivation, and student performance skill. The majority of students agreed that project assignments improved their grasp of concepts, boosted motivation, and enhanced teamwork. Students also reported increased problem-solving abilities and engagement with environmental conservation efforts. The study confirms that PjBL incorporating local wisdom positively influences botanical education by fostering deeper learning and real-world application. These findings offer valuable insights for developing culturally responsive and sustainable educational strategies.